Philosophy in the New Century (Continuum Compact). - O''Hear, Anthony (Bloomsbury Publishing, 2004)
In this powerful re-examination of the purpose and direction of philosophy for the next century, Anthony O''Hear engages with our most pressing questions: Is there knowledge outside of science? Does religion still have meaning and coherence today? What is beauty, and why do so few contemporary artists believe in it? Contemporary philosophy mostly divides into the technical approach of the Anglo-Americans, which is inaccessible to most, and the oracular obscurantism of the Continental approach, which does violence to sense and reason. O''Hear argues that philosophy should work with the grain.